Dakwah dalam Budaya Nu Ham Tua’ di Amarasi NTT - Fuad Fauzi Horsan (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2020)
Methods and discussing Islamic da'wah in Indonesia are increasingly diverse and always interesting to study, because da'wah besides implementing Muslims in the implication of God's messages to His servants is also a deedification or concept that develops the development of the times. However, this research is more interested in traditional and conventional da'wah research carried out with heredity (inheritance) from the founder for his successors, such as in NTT Province especially in the Amarasi Kupang community, as the Da'wah Old Ham ". Therefore, the purpose of this study is to discuss the culture of propaganda in Nu Ham Tua 'in Amarasi, NTT through the discovery of Communication Ethnography. Regarding the short definition, Communication Ethnography is a temporary theory for exporting and describing certain values, cultures, customs, communities through communication (verbal and verbal) through the principle of SPEAKING. Selected speakers are leaders, members and cultural communities, Nu Ham Tua, participants and interviews, and data as validity. The results of the study describe the culture of Nu Ham Tua 'discussing the typical and very thick blend of Timorese (indigenous) and Arabic (as immigrant tribe) cultures, seen in instruments (verbal using native language, Amarasi and others combined with Arabic and nonverbal it looks like Arabic culture (embracing each other, kissing a muhrim friend when meeting), and mutual cooperation is also a deliberation that accepts the indigenous culture of Indonesia. So, the Nu Ham Tua 'genre can be called Da'wah based on local wisdom.